Knowledge, attitude and practice of breastfeeding in the north of Jordan: a cross-sectional study - Amarin Zouhair; Khader Yousef; Khassawneh Mohammad; Alkafajei Ahmad (BMC, 2006)
Abstract Background In Jordan, as in neighboring countries in the Middle East, higher education and higher employment rates in recent years among women have had an impact on traditionally based infant feeding. The objective of this study was to evaluate practice, knowledge and attitude to breastfeeding and to assess factors associated with breastfeeding among women in the north of Jordan. Methods A cross sectional study was carried out between 15 July 2003 and 15 August 2003. A total of 344 women with children aged between 6 months and 3 years from five different villages in the north of Jordan were randomly selected and interviewed. Information regarding participants' demographics, infant feeding in first six months of life, knowledge and attitude towards breastfeeding was collected. Results Full breastfeeding was reported by 58.3%, mixed feeding was reported by 30.3% and infant formula feeding was reported by 11.4%. Almost one third of the full breastfeeding group did so for 6-12 months, and almost two thirds did continue breastfeeding for more than one year. Employed women were more likely not to practice full breastfeeding compared to unemployed women (odds ratio 3.34, 95% CI 1.60, 6.98), and women who had caesarian delivery were more likely not to practice full breastfeeding compared to those who had vaginal delivery (odds ratio 2.36, 95% CI 1.17, 4.78). Jordanian women had a positive attitude but work place and short maternity leaves had a negative impact on breastfeeding. Conclusion This study showed that a high proportion of Jordanian women did breastfeed for more than one year. However, working women and those who deliver by caesarean section were less likely to breastfeed. It is speculated that adopting facilitatory measures at hospitals and work place could increase the rate of full breastfeeding.